La dimension interculturelle des littératures francophones contemporaines dans l’enseignement/apprentissage du FLE - Gałan, Beata; Malela , Buata (Neofilolog, 2022)
The purpose of this article is to examine the issue of interculturality in contemporary Francophone literatures in the language classroom. As a tool of a humanist and intercultural education, the purpose of which is based on the awareness of cultural diversity and dialogue with the alterity, the literary text thus becomes a mediator in the development of intercultural competence. To illustrate this hypothesis, three texts will serve as a reference for this purpose: Dans le ventre du Congo (2021) by Blaise Ndala which tells the story of the conflictual relationship between Belgium and the colonized Congo; Les Impatientes (2020) by Djaili Amadou Amal which evokes the problem of violence against Cameroonian women, while La dynastie des boiteux. Zoonomia (2018) by Bessora deals with the figure of a Reunionese naturalist explorer of colonized Africa.